Lunar Heat Flow: Global Predictions and Reduced Heat Flux. Issue 9 (29th August 2022) - Siegler, Matthew; Warren, Paul; Franco, Katelyn Lehman; Paige, David; Feng, Jianqing; White, Mackenzie
Abstract: Geothermal heat flux of a body provides a unique look into its internal composition. The geothermal heat flux of the Moon is believed to vary primarily due to the distribution of radiogenic materials both spatially and vertically through the lunar crust. Here, we combine available global orbital, landed mission, returned sample, and meteorite data to produce a forward model of lunar heat flux consistent with present data. This provides a framework for future geothermal and geochemical measurements over the lunar surface, which can be tied back to global radiogenic and refractory element composition. We develop a model of the Moon as a single heat flux province represented by ∼60% of the Lunar Prospector Gamma‐Ray Spectrometer surface Th value or equivalently a 21.5 km thick layer with surface Th values. The zero‐thorium intercept, or "reduced heat flux, " of these models is approximately 5 m Wm −2, implying the net heat flux from the mantle is at or below this value. With an estimated Urey ratio between 0.65 and 0.73, this equates to a mantle thorium concentration of ∼19–∼25 ppb. This model suggests a bulk thorium concentration of approximately 50.5 ± 5.5 ppb. This value is based on the heat flux that would be obtained from a C Th / C U = 3.7, C K / C U = 2, 000 = or equivalently 13.7 ± 1.5 ppb of uranium and 27.2 ± 3.0 ppm potassium. Plain Language Summary: The heat flowing out of the lunar interior provides a window into the composition and temperatures of the lunar interior. Most of this heat is produced by radioactive elements in the crust (uranium, thorium, etc.). Across the Moon, both the crustal thickness and concentration of radioactive elements can change dramatically. Crustal thickness was measured in detail by the GRAIL (∼2012) and surface radioactive element concentration by Lunar Prospector (1999) missions. Both crustal thickness and radioactive elements were found to change regionally, with the near side region known as Procellarum being a major oddball with very thin crust and high concentrations of radioactive rocks. Here, we make models to predict how the heat flux of the Moon will vary from place to place to match both Apollo era and future heat flux measurements. The few measurements we have provide a biased view of what the Moon and a whole is made of. These models will aid in deciding where to land future lunar missions measuring heat flux or returning samples to best constrain the composition of the entire Moon. Key Points: We produce a self‐consistent forward model of lunar surface heat flux This models can provide a basis for future, targeted heat flux measurements We provide a best fit lunar bulk, crustal, and mantle radiogenic element composition consistent with present day data